Sustainability and private investors - Bonnie Buchanan; Hanna Silvola; Emilia Vähämaa (Bank of Finland, 2023)
Private investors are an increasingly important voice in sustainability challenges. We examine investors' attitudes and behavior towards sustainable investing through a survey of 5,030 Finnish private investors. We document that 60 percent of all respondents consider environmental, social, and governance (ESG) factors when making investment decisions. Our results indicate that women and millennials are more likely to follow sustainable investment strategies than investors on average. We also find that language background, location and education levels influence investment behavior. Moreover, our findings suggest that both sustainable and traditional investors are willing to take risks in their investment strategy. We also report the effects of the COVID pandemic on investor behavior and find that investors who started investing during the pandemic are less likely to choose traditional investment strategies. Our findings have implications for financial market participants and policymakers.
Keywords: G01; G21; G30; M14; 330; private investors; sustainability; investment strategies; ESG; risk-taking; COVID-19